Saint Marc : enjeux communautaires et dynamiques politiques - Sandrine Keriakos (Conserveries Mémorielles)
The figure of Saint Marc is central in the Egyptian christianity. The very context of the return of his relics in 1968, in a time marked by the political sidelining of the Coptic population and a spiritual revival within it, shows the prevalence of political stakes over the religious dimension, notably because of Nasser's will to stage national unity beyond denominational divisions. This episode shows how the worship of saints in the Coptic church depends on the social reality of the community and on its integration with the nation.